Linking collaboration and integration to risk and performance in supply chains via a review of literature reviews. Issue 5 (2nd September 2014) - Kache, Florian; Seuring, Stefan
Abstract : Purpose: – This paper aims to assess the links among these supply chain constructs by conducting a full-scale systematic review of all supply chain management (SCM) literature reviews published in ten leading logistics, SCM and operations management journals from 1989 to 2012. Collaboration and integration are as central to SCM as risk and performance management. Design/methodology/approach: – The authors apply content analysis to execute the systematic literature review on the sample of 103 articles, supplemented by contingency analysis. These approaches guarantee a replicable, rigorous and transparent research process and minimize researcher bias. The analytical categories required for the content analysis are defined along the constructs of collaboration/integration and risk/performance. Findings: – As can be expected, the review highlights the key role of the two constructs in SCM. In this light, the research claims to provide statistical evidence of a link between the constructs of collaboration/integration and risk/performance, most notably between collaboration and performance, information sharing and rewards sharing, as well as integration and supply chain performance. Research limitations/implications: – The study assesses the link between the constructs of collaboration/integration and risk/performance through research embedded in literature reviews, pinpointing research gaps and potential future research directions in the field. Contributing to SCM theory building, a thorough review provides statistical proof of the link between collaboration/integration and risk/performance. Originality/value: – Although numerous literature reviews have been conducted in the past on the SCM constructs of collaboration/integration and risk/performance, no full review of literature reviews aiming to test a theoretical link in the here presented form has yet been undertaken to the authors' knowledge.